Specific amygdala response to masked fearful faces in post-traumatic stress relative to other anxiety disorders. Issue 7 (27th September 2017) - Neumeister, P.; Feldker, K.; Heitmann, C. Y.; Buff, C.; Brinkmann, L.; Bruchmann, M.; Straube, T.
Abstract: Background: Altered amygdala activation to fear-related stimuli has been proposed to be a potential neural correlate of heightened threat sensitivity in anxiety- and stress-related disorders. However, the role of stimulus awareness and disorder specificity remains widely unclear. Here we investigated amygdala responses to conscious and unconscious fearful faces in patients suffering from panic disorder (PD), generalized anxiety disorder (GAD), or post-traumatic stress disorder (PTSD) and in a large sample of healthy controls (HC). Methods: During event-related functional magnetic resonance imaging participants ( n = 120; 20 PD, 20 GAD, 20 PTSD, 60 HC) were confronted with briefly presented fearful faces, neutral faces, and non-faces in a backward masking paradigm. The design allowed for the analysis of trial-by-trial face detection performance and amygdala responses to fearful v. neutral faces. Results: All participants exhibited increased amygdala activation to fearful v. neutral faces during conscious trials. Specifically during unconscious face processing, the PTSD, compared with all other groups, showed higher right basolateral (BLA) amygdala activity to fearful v. neutral faces. Conclusions: The present study shows that BLA amygdala hyperactivity during unconscious, but not conscious, processing of fearful faces differentiates PTSD from the investigated disorders. This finding suggests an automatic and specific neural hyper-responsivity to general fear cues in PTSD and supports the idea of categorical differences between PTSD and other anxiety-related disorders.